THE ANALYSIS OF SELECTED QUALITY CRITERIA OF SUBURBAN BUS TRANSPORT - Jurkovicova, Hana (Doprava a spoje, 2012)
Currently is a very important problematic the quality of the bus stops. In the article is processed the analysis of selected quality criteria of suburban bus transport. The article deals with the definition of the selected quality criteria. The selected quality criteria are evaluated and graphically processed. In the article is also evaluated of the analysis.